Return to volcano town reassessing the 1937-1943 volcanic eruptions at Rabaul - Johnson, Robert W. 1941-; Threlfall, Neville A. (ANU Press/The Australian National University, 2023)
"Wally Johnson and Neville Threlfall re-examine the explosive volcanic eruptions that in 1937-43 killed more than 500 people in the Rabaul area of East New Britain, Papua New Guinea. They reassess this disaster in light of the prodigious amount of new scientific and disaster-management work that has been undertaken there since about 1971, when strong tectonic earthquakes shook the area. Comparisons are made in particular with volcanic eruptions in 1994-2014, when half of Rabaul town was destroyed and then abandoned. A striking feature of historical eruptive periods at Rabaul is the near-simultaneous activity at Vulcan and Tavurvur volcanoes, on either side of Rabaul Harbour. Such rare 'twin' eruptions are interpreted to be the result of a common magma reservoir beneath the harbour. This interpretation has implications for ongoing hazard and risk assessments and for volcano monitoring in the area"--
Sequel to: Volcano town : the 1937-43 eruptions at Rabaul. Bathurst, N.S.W., Australia : R. Brown, ©1985
Keywords: Geschichte 1937-1943; Eruption; Papua-Neuguinea; Volcanism / Papua New Guinea / Rabaul; Volcanic eruptions / Papua New Guinea / Rabaul / History / 20th century; Emergency management / Papua New Guinea / Rabaul; Éruptions volcaniques / Papouasie-Nouvelle-Guinée / Rabaul / Histoire / 20e siècle